2017
DOI: 10.1007/s00264-017-3729-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for surgical site infection following open reduction and internal fixation of adult tibial plateau fractures

Abstract: The SSI incidence was high (5.7%) after surgical tibial plateau fractures by ORIF and open fracture, operative time, and smoking were identified as independent related risk factors. Therefore, we recommend that a smoking cessation program is introduced immediately at the time of admission to hospital. More reasonable management strategies on open injury should be utilized to reduce the SSI rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 27 publications
2
36
1
Order By: Relevance
“…Among the complications, SSI was the most common one. Previous literature had reported that SSIs developed at 2-14.2% of patients after they underwent ORIF, half of which were deep infections [5][6][7]. Consequently, patients had to be re-admitted or even re-operated to replace or remove internal fixtures to treat the infection.…”
Section: Introductionmentioning
confidence: 99%
“…Among the complications, SSI was the most common one. Previous literature had reported that SSIs developed at 2-14.2% of patients after they underwent ORIF, half of which were deep infections [5][6][7]. Consequently, patients had to be re-admitted or even re-operated to replace or remove internal fixtures to treat the infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the cases of bladder or pelvic diaphragm, the surgical site for the abdomen and pelvis has open communication. Risk factors for orthopedic SSI include prolonged operative duration and open fracture(s) [12,13]. After DCL, the route for the pelvic approach is easily contaminated and, in fact, is expected in long operations for complex fracture(s).…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 meta-analysis including 7925 patients found the incidence of superficial and deep surgical site infections after tibial plateau fracture repairs to be 4.2% and 5.9%, [54][55][56]125], compartment syndrome [27,[54][55][56], smoking [55,56,125], alcohol intake [126], definitive external fixation [56,94] and intraoperative duration approaching 3 h [54,56,125]. A recent article found a strong correlation between a significantly higher peak of C-reactive protein (CRP) >100 μg/ mL on postoperative day 3 and the development of surgical site infections in tibial plateau patients [127].…”
Section: Surgical Site Infectionmentioning
confidence: 99%